Cellulose Synthesis and Cell Expansion Are Regulated by Different Mechanisms in Growing Arabidopsis Hypocotyls. Issue 6 (26th May 2017) - Ivakov, Alexander; Flis, Anna; Apelt, Federico; Fünfgeld, Maximillian; Scherer, Ulrike; Stitt, Mark; Kragler, Friedrich; Vissenberg, Kris; Persson, Staffan; Suslov, Dmitry
Abstract : The production of cellulose in the plant cell wall is controlled by metabolic signals, while the expansion of cells is regulated by changes in cell wall properties controlled by the biological clock. Abstract: Plant growth is sustained by two complementary processes: biomass biosynthesis and cell expansion. The cell wall is crucial to both as it forms the majority of biomass, while its extensibility limits cell expansion. Cellulose is a major component of the cell wall and cellulose synthesis is pivotal to plant cell growth, and its regulation is poorly understood. Using periodic diurnal variation in Arabidopsis thaliana hypocotyl growth, we found that cellulose synthesis and cell expansion can be uncoupled and are regulated by different mechanisms. We grew Arabidopsis plants in very short photoperiods and used a combination of extended nights, continuous light, sucrose feeding experiments, and photosynthesis inhibition to tease apart the influences of light, metabolic, and circadian clock signaling on rates of cellulose biosynthesis and cell wall biomechanics. We demonstrate that cell expansion is regulated by protein-mediated changes in cell wall extensibility driven by the circadian clock. By contrast, the biosynthesis of cellulose is controlled through intracellular trafficking of cellulose synthase enzyme complexes regulated exclusively by metabolic signaling related to the carbon status of the plant and independently of the circadian clock or light signaling.